Replenishing NAD+ content reduces aspects of striated muscle disease in a dog model of Duchenne muscular dystrophy - Déborah Cardoso; Inès Barthélémy; Stéphane Blot; Antoine Muchir (Skeletal Muscle, 2023)
Abstract Duchenne muscular dystrophy (DMD) is an X-linked disease caused by mutations in DMD gene and loss of the protein dystrophin, which ultimately leads to myofiber membrane fragility and necrosis, with eventual muscle atrophy and contractures. Affected boys typically die in their second or third decade due to either respiratory failure or cardiomyopathy. Among the developed therapeutic strategies for DMD, gene therapy approaches partially restore micro-dystrophin or quasi-dystrophin expression. However, despite extensive attempts to develop definitive therapies for DMD, the standard of care remains corticosteroid, which has only palliative benefits. Animal models have played a key role in studies of DMD pathogenesis and treatment development. The golden retriever muscular dystrophy (GRMD) dog displays a phenotype aligning with the progressive course of DMD. Therefore, canine studies may translate better to humans. Recent studies suggested that nicotinamide adenine dinucleotide (NAD+) cellular content could be a critical determinant for striated muscle function. We showed here that NAD+ content was decreased in the striated muscles of GRMD, leading to an alteration of one of NAD+ co-substrate enzymes, PARP-1. Moreover, we showed that boosting NAD+ content using nicotinamide (NAM), a natural NAD+ precursor, modestly reduces aspects of striated muscle disease. Collectively, our results provide mechanistic insights into DMD.